Mapping of crustal scale tectonic boundaries in the Ossa-Morena Zone using reprocessed IBERSEIS reflection seismic data - Kashubin, A.; Juhlin, Christopher (Elsevier BV, 2010)
The IBERSEIS deep seismic reflection profile imaged crustal scale structures in the SW Iberian Variscan belt, crossing the South Portuguese Zone, the Ossa-Morena Zone and the Central Iberian Zone in Spain. Two subsets of the profile, corresponding to the South Portuguese Zone-Ossa-Morena Zone and the Ossa-Morena Zone-Central Iberian Zone tectonic contacts, have been reprocessed with the aim of investigating the influence of cross-dip and to better image steeply dipping features. Alternative strategies for binning midpoints into common depth point (CDP) bins using different azimuths were examined for synthetic data. We show that the choice of the CDP-processing line and the bin azimuth orientation has a significant impact on the normal moveout and dip-moveout velocities and is crucial to optimizing the quality of the stacked seismic image along the crooked profile. Multi-azimuth binning, normal moveout/dip-moveout, and migration velocity analysis on synthetic and real data show the presence of clear sub-vertical upper crustal structures near the South Portuguese Zone-Ossa-Morena Zone suture, the Aroche fault. This sub-vertical reflectivity that was not imaged earlier, projects into a location in the lower crust with low reflectivity. © 2010 Elsevier B.V.